2008
DOI: 10.1111/j.1651-2227.2008.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of nomograms and reference ranges for intra‐cranial ventricular dimensions and ventriculo‐hemispheric ratio in newborns by ultrasonography

Abstract: Intra-cranial ventricles increase in size with GA but this increase is limited to only a few mm and is proportional to increment in brain tissue. Nomograms and regression equations of AHW, TOD and widths of third and fourth ventricles can assist in objectively assessing ventricular sizes. The almost uniform VHR can be used to screen ventricle size while suspecting hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 16 publications
3
61
2
2
Order By: Relevance
“…There are also similar reports regarding other inter-ventricular dimensions, such as third ventricle width, fourth ventricle width, and fourth ventricle length (5,16). However, the Sondhi et al study (11) demonstrated a marked increase in TOD and AHW with progression of GA.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…There are also similar reports regarding other inter-ventricular dimensions, such as third ventricle width, fourth ventricle width, and fourth ventricle length (5,16). However, the Sondhi et al study (11) demonstrated a marked increase in TOD and AHW with progression of GA.…”
Section: Discussionmentioning
confidence: 71%
“…Whether AHW correlated with GA is controversial, several reports (5, 8, 13) similar to our results showed that AHW remained constant with increase in GA. Our study also showed just minimal change in AHW with birth weight. In most of the reports (5,8,11), the AHW is less than 3 mm. It is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ventricular dilatation was estimated according to the measurement of anterior horn width and of the thalamo-occipital distance. 9,10 The parenchymal echogenicity in the periventricular areas was defined as periventricular hyperechogenicity (PHE) when isoechogenic/hyperechogenic to the choroid plexus.…”
Section: Methodsmentioning
confidence: 99%